2018
DOI: 10.1016/j.pec.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Improving youth question-asking and provider education during pediatric asthma visits

Abstract: Providers/practices should consider having youth complete question prompt lists and watch the video with their parents before visits to increase youth question-asking during visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Using the recordings of patient–provider encounters, this study found that providers rarely included youth or caregiver input into the asthma management treatment regimens, 2.5% and 3.3% of visits, respectively. Although our intervention significantly increased the child’s question-asking and provider education about asthma and its treatment, 18 it did not increase the frequency with which providers included youth or caregiver input into treatment regimens. Future research should design and test other ways to increase youth and caregiver inputs into asthma treatment regimens, particularly when there is a treatment decision to be made involving more than one reasonable treatment option.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Using the recordings of patient–provider encounters, this study found that providers rarely included youth or caregiver input into the asthma management treatment regimens, 2.5% and 3.3% of visits, respectively. Although our intervention significantly increased the child’s question-asking and provider education about asthma and its treatment, 18 it did not increase the frequency with which providers included youth or caregiver input into treatment regimens. Future research should design and test other ways to increase youth and caregiver inputs into asthma treatment regimens, particularly when there is a treatment decision to be made involving more than one reasonable treatment option.…”
Section: Discussionmentioning
confidence: 86%
“…The effectiveness of the intervention on this outcome may be due, at least in part, to the fact that youth in the intervention arm asked more questions of providers and received more provider explanations and education about asthma than those in the control arm. 18 This improved patient–provider communication likely played a role in how youth perceived their providers’ decision-making style, even in the absence of direct input into treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is an important transitional period when youth gradually shift toward managing their chronic disease on their own. 1 Adolescents often show limited involvement in medical visits, especially when parents are reluctant to relinquish control of the visit and allow the adolescent to participate more in the discussion. 2 However, adolescents may learn selfmanagement of their disease more effectively if they can have higher-quality conversations with their providers that result in their concerns being addressed.…”
Section: To the Editormentioning
confidence: 99%
“…We previously reported that youth in the intervention group were significantly more likely to ask questions about medications, triggers, and environmental control than youth in the usual care group and were more likely to be educated by their providers about rescue medications, triggers, and environmental control during visits. 14 This current analysis examines (1) whether the question prompt list with video intervention increases the likelihood that youth who reported 1 or more asthma medication problems ask 1 or more questions about medications during their baseline pediatric visits and (2) how the intervention and question-asking during the baseline visit are associated with whether youth and their caregivers still reported 1 or more asthma medication problems 6 months later.…”
mentioning
confidence: 99%